Pembentukan Desa Tangguh Bencana Covid-19 untuk Antisipasi Penyebaran dan Dampaknya di Provinsi Sulawesi Tenggara - Jaya, Laode M Golok; Ngii, Edward; Mangidi, Uniadi; Azikin, Thahir; Welendo, La (Vokasi Universitas Halu Oleo, 2020)
The spread of the Corona virus (Covid-19) has recently become increasingly worrying, not only because of the inadequate handling due to the lack of mass rapid tests and the obstacle to the examination method using polymerase chain reaction (PCR) techniques. On the other hand, the habit of people who ignore and underestimate the spread of Covid-19 infection has become the main trigger for the increasing number of positive patients of Covid-19. This is even more worrying if the scale of our review is not only urban but also rural, where the potential for exposure to Covid-19 is getting bigger. Therefore, Halu Oleo University through the Integrated Community Service program (KKN) Thematic Prevention of Covid-19 has a big agenda of increasing public awareness both in cities and in rural areas who are very prone to exposure to Covid-19 to minimize the impact that occurs due to the spread of Covid-19. The purpose of this activity is to form a Covid-19 Disaster Resilient Village to anticipate its spread and impact in Southeast Sulawesi Province. This KKN is a multidisciplinary activity from various scientific fields involving students and lecturers from various departments. The method implemented is socialization as an effort to increase public awareness through social media that is easily accessed and understood by the community while still implementing social distancing and with strict health protocols, involving village and community officials. Another method is to collect data on the profiles of people who are vulnerable to exposure and have an impact on their health and economy, in addition to physical activities such as spraying with disinfectants at houses of worship. Other methods carried out include making booklets using local languages, and making tutorials on using Zoom and Google Meet online media meetings so that learning activities of school students and village officials can continue during the Covid-19 pandemic.The results of this KKN Thematic activity are expected to become a learning medium for students as part of the Merdeka Campus Program, building villages that are resilient to the Covid-19 disaster, maintaining the economy and community activities, and become a forum for community service for lecturers.